Real time telemedical health care systems with wearable sensors - Fajingbesi, Fawwaz Eniola; Olanrewaju, Rashidah Funke; Pampori, Bisma Rasool; Khan, Sheroz; Yaacob, Mashkuri (Gyancity Research Lab, 2017)
The time between detection and response to chronic diseases could go a long way in saving lives. The current trend in health monitoring systems is to move from the hospital centered device to eventually portable personal devices. Hence,Telemedical health care involves the remote delivery of medical care service to either out-of-hospital or admitted patients through wireless network and computer information technology. This paper systematically reviews the most recent works in telemedical health care system to propose a more efficient model. The focus is more on wearable sensors and devices with most attention given to cardiovascular patients in recent times. The huge literature available reflects the size of activity and attention given to telemedicine. The reviewed works are published within the last five years. Furthermore, the proposed systems are compared in terms of their connectivity, targeted application, type of sensor used, etc. Our study reveals Telemedicine to be a profound field with researchers from multidisciplinary sectors. However, there are still many gaps that need to be filled before maturity. Factors such as efficient wireless transmission, cyber data security, sensor design and integration, device miniaturization and intelligent algorithm for multi parameter data fusion require further considerations.